Differential effects of the working alliance in family therapeutic home‐based treatment of multi‐problem families. Issue 1 (27th October 2014) - Bachler, Egon; Frühmann, Alexander; Bachler, Herbert; Aas, Benjamin; Strunk, Guido; Nickel, Marius
Abstract : Families with a low socioeconomic status play an increasingly significant role in health services, research and social policy. The present outcome research study is a pre/post naturalistic study of home‐based therapeutic work with multi‐problem families (MPF), as conducted by Therapeutisch Ambulante Familenbetreung, an integrative family therapy with a structure‐related, mentalization‐based, psychoanalytic orientation. With a mean treatment duration of 75.7 weeks, 379 families showed significant psychological improvement on 10 scales concerning patient–therapist collaboration, treatment expectancy and psycho‐social outcome measures with a medium to large effect size for all parameters (range: .35–1.49). About two‐thirds of the sample improved by two SD on individually set treatment goals, further supporting the clinical significance of the therapeutic effect of home‐based family treatment. Improvements in goal‐directed collaboration and treatment expectancy are shown to be related to clinical improvement. Structural family therapy interventions for families with multiple problems thus benefit from individually setting goals and improving their self‐efficacy and problem‐solving by means of improved treatment expectancy. Practitioner's points: MPF constitute a significant problem in healthcare and costs (burden of disease). The treatment of MPF is considered relatively difficult. Improvements to the process quality (working alliance, treatment expectancy) increase the quality of the results of home‐based treatment of MPF.